Immediate Versus Delayed Repair of Destructive Bowel Injuries in Patients with an Open Abdomen. Issue 5 (May 2015) - Raines, Alexander; Garwe, Tabitha; Albrecht, Roxie; Havron, William; Hoge, Stephen; Ademola, Adeseye; Glenn, Jacquelyn; Motghare, Prasenjeet; Irvan, Jeremy; Patel, Arpit; Lees, Jason
Trauma surgeons frequently encounter destructive bowel injuries. The timing of the repair of the bowel injury should be performed in patients with planned open abdomen management and second-look laparotomy has not been specifically addressed. Our primary objective was to determine if there was a significant difference in the incidence of major complications between immediate and delayed repair among patients with traumatic bowel injuries and planned open abdomens. This was a retrospective cohort study of adult patients with traumatic bowel injuries treated between 2001 and 2011 and who underwent laparotomy and were left with an open abdomen with a planned second operation. Pediatric patients (age less than 15 years) and patients who died in the first 24 hours of admission were excluded. The primary exposure of interest was dichotomously defined based on either definitive repair of the bowel injury during the initial trauma operation (immediate) or definitive repair during a subsequent surgery (delayed). Major complications were defined as enterocutaneous fistula, dehiscence, and abscess. Ninety-two patients met study eligibility. Of these, 50 (54%) underwent immediate bowel repair. Univariate analysis suggested no significant differences in the proportion of major complications between the two groups. After adjusting for Injury Severity Score, penetrating injury, initial base deficit, and presence of colon injury, there was no statistical difference in incidence of major complications between the two groups. Patients undergoing immediate versus delayed repair of traumatic bowel injuries and who are left with an open abdomen have comparable outcomes in terms of major complications.